2014
DOI: 10.1063/1.4862691
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation dynamics of nitromethane and methyl nitrite by infrared multiphoton dissociation imaging with quasiclassical trajectory calculations: Signatures of the roaming pathway

Abstract: We combine the techniques of infrared multiphoton dissociation (IRMPD) with state selective ion imaging to probe roaming dynamics in the unimolecular dissociation of nitromethane and methyl nitrite. Recent theoretical calculations suggest a "roaming-mediated isomerization" pathway of nitromethane to methyl nitrite prior to decomposition. State-resolved imaging of the NO product coupled with infrared multiphoton dissociation was carried out to examine this unimolecular decomposition near threshold. The IRMPD im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
3
46
0
Order By: Relevance
“…40 Such a roaming-mediated isomerization pathway was also found in nitrobenzene 42 and nitromethane 43,44 to account for a significant yield of the NO elimination. For instance, Suits, Bowmen and coworkers 45 carried out the infrared multiphoton dissociation of nitromethane to examine this unimolecular decomposition near threshold. They found that the roaming-mediated isomerization pathway dominates the NO loss channel, yielding a small translational energy release and a feature of the L-doublet propensity of NO, favoring an unpaired electron lying in the pp orbital perpendicular to the plane of rotation.…”
Section: Photodissociation Mechanismmentioning
confidence: 99%
“…40 Such a roaming-mediated isomerization pathway was also found in nitrobenzene 42 and nitromethane 43,44 to account for a significant yield of the NO elimination. For instance, Suits, Bowmen and coworkers 45 carried out the infrared multiphoton dissociation of nitromethane to examine this unimolecular decomposition near threshold. They found that the roaming-mediated isomerization pathway dominates the NO loss channel, yielding a small translational energy release and a feature of the L-doublet propensity of NO, favoring an unpaired electron lying in the pp orbital perpendicular to the plane of rotation.…”
Section: Photodissociation Mechanismmentioning
confidence: 99%
“…These studies revealed three channels: (1) the unimolecular decomposition of nitromethane (CH 3 NO 2 ) to the methyl radical (CH 3 ) and to nitrogen dioxide (NO 2 ) 30,[35][36][37][38][39] via reaction (1) as well as (2) a roamingmediated nitromethane (CH 3 NO 2 )-methylnitrite (CH 3 ONO) isomerization in IRMPD studies followed by unimolecular decomposition via (2a) a radical pathway to the methoxy radical (CH 3 O) plus nitrogen monoxide (NO) (reaction (2a) and (2b)) through a molecular elimination pathway yielding formaldehyde (H 2 CO) plus nitrosylhydride (HNO) (reaction (2b)). [37][38][39][40][41] CH 3 NO 2 -CH 3 + NO 2 (1)…”
Section: Introductionmentioning
confidence: 99%
“…Roaming has now been reported for numerous reactions, as described in [83]. Extensive analyses of roaming have been reported for CH 3 CHO [85][86][87] and NO 3 [88][89][90] dissociation and isomerization in CH 3 NO 2 [91][92][93]. Roaming is expected to be important for hydrocarbon dissociation [94] and for C 3 H 8 → CH 3 + C 2 H 5 may lead to the possible disproportionation products CH 4 + C 2 H 4 and CH 2 + C 2 H 6 .…”
Section: (E) Roaming Dynamicsmentioning
confidence: 99%